Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'd like to know if the approach I took below (solving quadratic formula for function $u$) was valid.

Solve for $\theta$:

$2\cos \theta = 3\cos^2 \theta - 1$

Let $u = \cos \theta$:

$0 = 3u^2 - 2u - 1$

Apply quadratic formula:

$u = \frac{1\pm 2}{3}$

$\cos \theta_1 = 1, \cos \theta_2 = -\frac{1}{3}$

$\theta_1 = \arccos(1), \theta_2 = \arccos(-\frac{1}{3})$

I only wanted $\theta$ in $(0..\pi)$, which is $\theta_2$, which I happen to know is indeed the correct answer.

Again, what I'd like to know is if my approach was valid. Specifically, substituting a variable for a function, solving the quadratic equation for that variable, then solving for the function equal to that variable. It felt wrong, but gave the correct answer. Could I do this for any $u$, or was I just fortunate that $\cos \theta$ met some condition? I tried searching the web but everything I found talking about the quadratic formula only showed examples for $x$.

share|cite|improve this question
This is absolutely valid. In fact, there was no need to use the formula. We have $3\cos^2\theta-2\cos\theta-1\equiv (3\cos\theta+1)(\cos\theta-1)$. – Fly by Night Oct 9 '13 at 19:21
up vote 3 down vote accepted

This is absolutely valid. In fact, the quadratic formula was unnecessary. Just as factorsies to give $$3u^2-2u-1 \equiv (3u+1)(u-1),$$ we have the exactly analogous expression $$3\cos^2\theta-2\cos\theta-1 \equiv (3\cos\theta+1)(\cos\theta-1)$$ Solutions to $3\cos^2\theta-2\cos\theta-1=0$ are then given by $3\cos\theta+1=0$ or $\cos\theta-1=0$.

This works for all kinds of functions. For example $$\operatorname{e}^{2x}-3\!\operatorname{e}^x+2 \equiv \left(\operatorname{e}^x-1\right)\left(\operatorname{e}^x-2\right)$$ and so $\operatorname{e}^{2x}-3\!\operatorname{e}^x+2=0$ over the reals if, amd only if, $\operatorname{e}^x=1$ or $\operatorname{e}^x=2$, i.e. $x=0$ or $x = \ln 2$.

~~~ EDIT ~~~

In general, you may apply the formula. For example $$\cos^2\theta + 4\cos\theta + 1=0 \iff \cos\theta = -2\pm\sqrt{3}$$ $$2\ln^2x+3\ln x-4=0 \iff \ln x= -\tfrac{3}{4} \pm \tfrac{1}{4}\sqrt{31}$$

share|cite|improve this answer
thanks. if i remember correctly, one way to derive the quadratic formula is to try to factorize the generic problem. i was mainly just concerned about substituting an arbitrary function for x then applying the quadratic formula – Kip Oct 9 '13 at 19:42
@Kip The standard way to derive the formula is to "complete the square", e.g. to write $x^2+4x+1=0$ as $(x+2)^2-3=0$. Then $(x+2)^2=3$ and so $x=-2\pm\sqrt{3}$. This is different to factorising. To factorise, you would need to spot that $x^2+4x+1 \equiv (x+2-\sqrt{3})(x+2+\sqrt{3})$, i.e. spot the solution straight away. – Fly by Night Oct 9 '13 at 19:48

Your approach is absolutely correct, as long as the quantity $x$ (where $x$ is a variable, function, power of a variable, etc.) exactly matches at all terms.

This method is also applicable for solving an equation in multiple variables in terms of one of those variables.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.